Ethnomatematical connections between geometric concepts in the making of tortillas from Chilpancingo, Mexico - Rodríguez-Nieto, Camilo Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In the article, the ethnomathematical connections between geometric concepts evidenced in the elaboration of the tortilla by a merchant from Chilpancingo, Mexico are analyzed. The research was theoretically based on Ethnomathematics and the methodology was qualitative-ethnographic. The data were collected through a semi-structured interview, applied to a tortilla merchant from the city of Chilpancingo, Mexico. The results show the connections between the concepts (circumference-circle-cylinder), measurements, counts and sequences, which arise in the process of making, shaping and marketing the tortilla. The analysis of the practice of making tortillas, allowed to identify geometric concepts that provide tools to the teaching of school mathematics, from situations or tasks based on everyday life. Teachers are shown the existence of other ways of approaching the associated geometric concepts, using: paper, ruler, pencil and compass, together with the GeoGebra software that allows visualizing mathematical objects, and permanently evidence the connections established by a person in the graphical and algebraic-symbolic views.